Synthetic Inertia-Power Sharing in High Renewable Power Grids Through Vehicle-to-Grid Topology - Thongchart Kerdphol; Tossaporn Surinkaew; Issarachai Ngamroo (My University, 2024)
With the increasing integration of renewable energy sources (RESs), the overall inertia of the power system is expected to decline. The remaining inertia is crucial for regulating system frequency and mitigating excessive rates of change. The deployment of dispatchable loads, such as electric vehicles (EVs), offers a promising solution. This paper presents a synchronized inertia support framework utilizing a vehicle-to-grid (V2G) system through its bidirectional chargers. This concept is realized by integrating a large-scale energy storage system (ESS) composed of controllable EVs into an enhanced inertia emulation structure. The synthetic inertia control strategy has been refined to account for EV user convenience and synchronized state of charge (SOC) management, facilitating synchronized inertia power sharing. This approach enhances the grid's dynamic performance and resilience. Simulation results demonstrate that the proposed method effectively delivers rapid inertia support from the onboard ESS of EVs, improving frequency stability.
Keywords: Electric Vehicles and Infrastructure; Electric and Hybrid Vehicle Technologies; Transportation and Mobility Innovations